The 'Two Bridges Technique' for sternal wound closure. The use of vacuum‐assisted closure for the treatment of deep sternal wound defects: a centre‐specific technique. Issue 2 (12th February 2018) - Waked, Karl; Ballaux, Philippe; Goossens, Dominique; Cathenis, Koen
Abstract: The objective is to describe the 'Two Bridges Technique' (TBT), which has proven to be successful and has been the standard technique at our centre for vacuum‐assisted closure (VAC) of post‐sternotomy mediastinitis. An extensive literature search was performed in four databases to identify all published articles concerning VAC for post‐sternotomy mediastinitis. Several VAC methods have been used; however, no article has described our specific technique. TBT consists of a two‐bridges construction using two types of foam with different pore sizes, which ensures an equally divided negative pressure over the wound bed and stabilisation of the chest. This guarantees a continuous treatment of the sternal defect and prevents foam displacement. It maintains an airtight seal that prevents skin maceration and provides enough protection to avoid right ventricular rupture. The main advantage of TBT is the prevention of shifting or tilting of the foam during chest movements such as breathing or couching. Along with targeted antibiotic treatment, this alternative VAC technique can be an asset in the sometimes cumbersome treatment of post‐sternotomy mediastinitis.